Career destinations and views in 1998 of the doctors who qualified in the United Kingdom in 1993. - Lambert, T; Goldacre, M (2002)
OBJECTIVE: To report career destinations and views in 1998 of doctors who qualified in the United Kingdom (UK) in 1993. DESIGN: Postal questionnaire survey. SETTING: This study took place in the United Kingdom. SUBJECTS: All doctors who qualified in the UK in 1993. MAIN OUTCOME MEASURES: The percentage of doctors in each branch of medicine five years after qualification, and their views on their training and career opportunities. RESULTS: The NHS and universities in the UK employed 88% of respondents (men 90%, women 86%). UK general practice employed 24% of respondents (men 19%, women 28%). There were significant differences (P < 0.01) between the percentages of men and women working in the surgical specialties (men 28%, women 10%), paediatrics (men 8%, women 15%) and obstetrics and gynaecology (men 5%, women 10%). Respondents not in paid employment comprised 1.4% of men and 6.6% of women. 45% of respondents agreed that their postgraduate training was of a high standard, with 26% disagreeing and 29% unsure. 47% of specialist registrars felt their training was too short and 78% were concerned about the availability of consultant posts on completion. CONCLUSIONS: Although loss of doctors from the British workforce through emigration or unemployment is not increasing, our findings confirm a substantial shift away from careers in general practice. The number of home-trained GPs from this generation of doctors will be inadequate to meet service needs. GPs and hospital specialist doctors expressed concerns about quality of training, lack of careers advice, the shortness of specialist registrar training and availability of consultant posts on completion of training.